2020
DOI: 10.1371/journal.pone.0227971
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Early do-not-resuscitate orders in the intensive care unit and patient outcomes

Abstract: Background The use of Do-Not-Resuscitate (DNR) orders has increased but many are placed late in the dying process. This study is to determine the association between the timing of DNR order placement in the intensive care unit (ICU) and nurses' perceptions of patients' distress and quality of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
25
2
Order By: Relevance
“…In contrast to a study in which nurses were more comfortable giving opioids for pain management at the EOL [6], our study found that EDNR is associated with decreased narcotic use. We hypothesize that the shorter duration from DNR placement to death and shorter hospital LOS associated with EDNR allowed less time for physicians to address the family members on patients' comfort during the care.…”
Section: Hospital Carecontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to a study in which nurses were more comfortable giving opioids for pain management at the EOL [6], our study found that EDNR is associated with decreased narcotic use. We hypothesize that the shorter duration from DNR placement to death and shorter hospital LOS associated with EDNR allowed less time for physicians to address the family members on patients' comfort during the care.…”
Section: Hospital Carecontrasting
confidence: 99%
“…In theory, the DNR order itself should not directly impact care until the moment of cardiac arrest. However, one study found that EDNR directly influenced both resuscitative and ancillary care, with fewer invasive interventions being performed in the last week of life, including dialysis, mechanical ventilation, feeding tubes, and CPR, compared to those with LDNR and no DNR [6]. Another study on out-of-hospital cardiac arrest (OHCA) patients found that EDNR is associated with a significant decrease in potentially critical therapeutic options, including cardiac catheterization, bypass surgery, and blood transfusion after resuscitation, and is associated with less aggressive hospital care, fewer potentially beneficial procedures, and worse survival [3].…”
Section: Hospital Carementioning
confidence: 99%
See 1 more Smart Citation
“…Nava et al, investigating 6,008 patients in European respiratory intermediate care units and high-dependency units, found that merely 21% of patients received end-of-life decision, including withholding of treatment, DNR/do-not-intubate orders, and non-invasive MV (37). Furthermore, studies have shown that timely communication with families and the interprofessional collaboration for individualized balance between aggressiveness and responsiveness of care, which was recently reported by Rak et al through conducting a large and delicate ethnographic study in eight long-term acute care hospitals, are crucial in the end-oflife care among patients requiring PMV (39,40). Therefore, we think that the mortality prediction model and the illustration of main features attributed to high mortality in patients with PMV might indicate the need for timely communication regarding end-of-life issues.…”
Section: Discussionmentioning
confidence: 90%
“…In other hospitalized patient populations earlier goals of care conversations and DNR placement were linked to less intensive end-of-life care and better quality of life. 35,36 However, the effect of having a DNR and DNR placement timing on the relationship between dementia and end-of-life care intensity is unknown.…”
Section: Introductionmentioning
confidence: 99%